Hepatocyte Alterations and Impact on Reproduction among New Zealand White Female Rabbits Fed Diets with Varying Levels of Aflatoxin - Kitilit, J. B.; Mwaniki, D. M.; Magak, G. N. (Africa Environmental Review Journal, 2022)
Aflatoxin are poisonous compounds produced by fungi found in cereal grains and forage harvested or stored under humid-warm environmental conditions. Consumption of doses amounting to 20 -120 ppb of body weight per day can cause poisoning through an immediate damage on liver hepatocytes. Harmful effects of aflatoxin include their interference with both animal product production and reproductive functions. The current study sought to determine the histopathology of the liver by aflatoxin contained in the diet consumed by New Zealand white rabbits. Sixteen rabbits kept in cages were fed diets containing four levels of aflatoxin in four treatments 1 (0- level of aflatoxin), treatment 2 (100 ppb aflatoxin), treatment 3 (200 ppb aflatoxin) and treatment 4 (400 ppb aflatoxin) for a period of forty five days. The rabbits aged three months were kept in cages inside a housing structure with sufficient ventilation and 12 hour lighting daily. At the end of the feeding period, one rabbit from each treatment group was taken to anatomy and pathological laboratory, where it was humanely sacrificed and the liver harvested for histological examination. The liver tissue was sectioned and mounted on slides for microscopy. The results showed effects on the liver in all the treatment diets that contained aflatoxin. Marked focal inflammation and tissue infiltration in the periportal area of the liver were observed. The liver is the organ with the highest activation of oestrogen receptors in an animal’s body, but is dependent on the intake of sufficient amount of amino acids by the animal through its diet. Sufficient amount of oestrogen receptors, activate the secretion of Estrogen receptor alpha (ERα), which expresses itself in the uterus and ovary to cause the release of estrogen and synthesis of Insulin-like growth factor 1(IGF-1), the former activates the hypothalamus to release gonadotropic releasing hormone, which target the anterior pituitary gland for the release of gonadotrophs. Aflatoxin therefore, caused inflammatory reactions on hepatocytes and cell infiltration in rabbits in treatment 2, 3 and 4, but the pathological level was higher for the latter two treatments. Rabbit diets must not contain more than 100 ppb of aflatoxin to avoid its general effects on their reproduction.